2018
DOI: 10.1504/ijmp.2018.10008646
|View full text |Cite
|
Sign up to set email alerts
|

Perceived managerial and leadership effectiveness in Argentina and Mexico: a comparative study of effective and ineffective managerial behaviour

Abstract: The purpose of this study was to explore similarities and dissimilarities between perceptions of effective and ineffective managerial behaviour observed in private and public sector organisations in Argentina and Mexico respectively. The results of a qualitative cross-case/cross-nation comparative analysis of findings obtained from two emic replication studies of perceived managerial and leadership effectiveness previously carried out by the authors suggest that in both countries effective managers are perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…The purpose of our qualitative cross-case/cross-nation comparative study has been to search for similarities and dissimilarities across the three compared emic replication studies (cases) and to differentiate any identified local (context-specific) behavioral indicators of perceived managerial and leadership effectiveness from those identified as having potential for generic (context-general) applicability. A total of 39 geocentric behavioral indicators have been identified, which (a) challenge predominant discourse about the contingent nature of management and leadership, (b) support those who theorize the existence of the universal effective manager, and (c) provide what we believe to be the first body of indigenous South Korean empirical evidence suitable for use as an added case for further generalizing and refining a "universalistic" taxonomy of perceived managerial and leadership effectiveness that has been cumulatively developed by Author 1 with various co-researchers from other countries (see Hamlin, Patel, Ruiz, & Whitford, 2012 ) through a process of replication logic and multiple cross-case analysis (Eisenhardt, 1989 ).…”
Section: Introductionsupporting
confidence: 59%
“…The purpose of our qualitative cross-case/cross-nation comparative study has been to search for similarities and dissimilarities across the three compared emic replication studies (cases) and to differentiate any identified local (context-specific) behavioral indicators of perceived managerial and leadership effectiveness from those identified as having potential for generic (context-general) applicability. A total of 39 geocentric behavioral indicators have been identified, which (a) challenge predominant discourse about the contingent nature of management and leadership, (b) support those who theorize the existence of the universal effective manager, and (c) provide what we believe to be the first body of indigenous South Korean empirical evidence suitable for use as an added case for further generalizing and refining a "universalistic" taxonomy of perceived managerial and leadership effectiveness that has been cumulatively developed by Author 1 with various co-researchers from other countries (see Hamlin, Patel, Ruiz, & Whitford, 2012 ) through a process of replication logic and multiple cross-case analysis (Eisenhardt, 1989 ).…”
Section: Introductionsupporting
confidence: 59%
“…Yukl states that there is a segmentation of theoretical approaches and sought a reference that integrates the various contributions. Some researchers seek to identify the "global" or "universal" behaviors of the leader (Hamlin, 2002;Hamlin et al, 2012;Hamlin and Hatton, 2013;Kets de Vries et al, 2004;Yukl, 2012;Yukl et al, 2002). Yukl, Gordon and Taber present as a solution a hierarchical taxonomy consisting of three meta-categories of behaviors -"Task behavior, Relations behavior, Change behavior" (Yukl et al, 2002).…”
Section: Synthesis Of the Integrative Literature Reviewmentioning
confidence: 99%